(untitled) (The Planet, 2023)
Background: When a person commits suicide by hangingthemselves, they suffer death similar to that caused bysevere hypoxia caused by the ligature material tighteningaround the neck structures and cutting off ventilation to thelungs. Objective: To evaluate the prevalence and causes ofHanging Cases in Sylhet Osmani Medical College Hospital.Method: A study on hanging victims at Sylhet OsmaniMedical College from July 2015 to July 2017 was conductedretrospectively. The inquest report accompanying the deadbodies gathered data on 60 victims, including incidencelocations, times, causes of death, suspension type, andrelated information from attendants. Results: Mostparticipants were aged 21-30 and 66.67% were female. 35%of hangings were caused by marital discord. Dopatta wasthe top choice (50%) for ligature, with jute rope (18.3%)and shari (10%) following close behind. There were 43% on the right side, 40% on the left,10% towards the back of the neck, and 7% under the chin.. Neck injuries were observed inmost cases, including stretching and elongation in 70%, skin hemorrhage in 50%, and musclehemorrhage in 40%. In 36.67 % of the patients, the platysma and sternocledo mastoid musclesruptured. The majority of participants were right-handed. 50% of cases had a solitary ligaturemark, while 33.33% had a double mark, and 10% had a barely visible one. Conclusion:Younger women were found to be more prone to suicide by hanging. It’s the top cause ofrelationship turmoil. Most were right-necked and right-handed. Usually, patients have just oneligature mark. We require extensive research across multiple centers to ascertain our true stance.